Costs of production loss and primary health care interventions for return-to-work of sick-listed workers in Sweden. (24th July 2014) - Persson, Jan; Bernfort, Lars; Wåhlin, Charlotte; Öberg, Birgitta; Ekberg, Kerstin
Abstract: Purpose : The aim of this study was to investigate, from the perspective of society, the costs of sick leave and rehabilitation of recently sick-listed workers with musculoskeletal disorders (MSD) or mental disorders (MD). Methods : In a prospective cohort study, 812 sick-listed workers with MSD (518) or MD (294) were included. Data on consumption of health care and production loss were collected over six months from an administrative casebook system of the health care provider. Production loss was estimated based on the number of sick-leave days. Societal costs were based on the human capital approach. Results : The mean costs of production loss per person were EUR 5978 (MSD) and EUR 6381 (MD). Health care interventions accounted for 9.3% (MSD) and 8.2% (MD) of the costs of production loss. Corresponding figures for rehabilitation activities were 3.7% (MSD) and 3.1% (MD). Health care interventions were received by about 95% in both diagnostic groups. For nearly half of the cohort, no rehabilitation intervention at all was provided. Conclusions : Costs associated with sick leave were dominated by production loss. Resources invested in rehabilitation were small. By increasing investment in early rehabilitation, costs to society and the individual might be reduced. Implications for Rehabilitation: Resources invested in rehabilitation for sick-listed with musculoskeletal and mental disorders in Sweden are very small in comparison with the costs of production loss. For policy makers, there may be much to gain through investments into improved rehabilitation processes for return to work. Health care professionals need to develop rehabilitative activities aiming for return to work, rather than symptoms treatment only.